Factors That Affect Tax Aggressiveness With Good Corporate Governance as a Moderating Variable - Eka, Dian; Suryani Lating, Ade Irma; Yudhanti, Ashari Lintang; Romaisyah, Luqita; P.A.C, M.Nur Nama Arep (Journal of Accounting Science, 2024)
General Background: Taxation plays a crucial role in generating revenue for the Indonesian government, primarily through a self-assessment system that challenges taxpayers to report taxes accurately. Specific Background: However, the tax-to-GDP ratio has consistently fallen short of targets, highlighting the need for enhanced compliance and governance. Knowledge Gap: Previous studies on tax aggressiveness have yielded inconsistent results regarding the effects of managerial character, political connections, and firm size, moderated by corporate governance, on tax strategies. Aims: This study examines the impact of managerial character, political connections, and firm size on tax aggressiveness, with a focus on corporate governance as a moderating factor in manufacturing companies listed on the Indonesia Stock Exchange between 2019-2021. Results: Managerial characteristics and firm size were found to have significant positive effects on tax aggressiveness. However, executive compensation and political connections showed no significant impact. Corporate governance, represented by audit quality, moderated the relationship between managerial characteristics and firm size on tax aggressiveness but did not influence the relationships involving executive compensation and political connections. Novelty: This study uniquely highlights the moderating role of corporate governance in shaping tax strategies in the Indonesian context, providing empirical evidence of its efficacy. Implications: The findings suggest that enhancing audit quality within corporate governance frameworks could mitigate aggressive tax practices, thereby aiding policymakers and stakeholders in developing strategies to improve tax compliance.